Benarkah Aristoteles dan Confucius menganut ajaran tauhid?‎ - Much Hasan Darojat (Universitas Darussalam Gontor, 2020)
This article aims to delineate the weakness of Osman Bakr's notions who claims that al-Ghazali regarded Aristotle to have tawhidic belief. This opinion may lead to different views because it leads to confusion concerning this great figure of ×ujjat al-Islâm. In al-Ghazali’s various works, the author does not find such a claim. He merely classified the philosophers with their backgrounds, without showing any belief of their monotheistic principles. In addition, the author also refutes Osman's opinion, which says that if a Muslim recognizes Confucius's prophethood, he will not contradict to any Islamic teachings. This opinion seems to invite readers to acknowledge his prophethood even as a Muslim intellectual. These two figures are often the objects of study by number of researchers in the fields of philosophy and religion. However, a Muslim scholar must be able to place them according to their role and contribution critically and carefully. The author concludes that the above-mentioned claims are baseless and inaccurate arguments, so they deserve to be rejected. Number of works by those two figures do not show the arguments of the claim. In this article, the author applies the analytical text and descriptive analysis method by analysing the main sources that are relevant to the context of the issue.